Observation of Dental Structures Under the Influence of Acids: An In-Vitro Forensic Study - Juhi Bali; Dharmesh Vasavada; Rashmi G.S. Phulari; Mehul Ojha; Yashraj Rathore (Indian Journal of Forensic Medicine and Pathology, 2025)
Context: Forensic odontology plays a vital role in human identi𿿿cation, particularly when conventional methods are hindered by decomposition or trauma. Understanding the effects of various environmental factors on teeth is crucial for effective forensic analysis. Aims: The study aim to evaluate the effects of three different acids - 37% Hydrochloric Acid (HCl), 65% Nitric Acid (HNO3 ), and 98% Formic Acid (HCOOH) - on extracted permanent mandibular 𿿿rst molars, focusing n oncarious, carious, and Class I composite𿿿lled teeth. Methods and Material: A total of 45 extracted permanent mandibular𿿿rst molars we subjected to acid solutions each of 30 ml for different durations ranging from 15 minutes to 24 hours. The teeth were categorized into non-carious, carious, and Class I composite-𿿿lled groups. Morphological, microscopic, and raiographic eluations were conducted at various time intervals to assess the effects of acid exposure on the dental tissues and restorations.Results: The study found that acid exposure led to signi𿿿cant changes inthemorphology, microscopic structure, and radiographic appearance of both dental tissues and restorations. Variations in the rate of degradation were observed depending on the type of acid and the condition of the teeth. Conclusions: The results offer valuable insights into the effects of acid exposure on teeth, particularly in forensic odontology. Understanding these effects is critical for evaluating the durability of dental structures and restorations in forensic identi𿿿cation processes, where teeth are frequently used as a primarymeans of identi𿿿cation.